Induction of GABAergic Postsynaptic Differentiation by α-Neurexins - Kang, Yunhee (2007)
β-Neurexin and neuroligin cell adhesion molecules contribute to synapse development in the brain. The longer α-neurexins function at both glutamate and γ-aminobutyric acid (GABA) synapses in coupling to presynaptic calcium channels. Binding of α-neurexins to neuroligins was recently reported, but the role of the α-neurexins in synapse development has not been well studied. Here we report that in COS cell neuron coculture assays, all three α-neurexins induce clustering of the GABAergic postsynaptic scaffolding protein gephyrin and neuroligin 2 but not of the glutamatergic postsynaptic scaffolding protein PSD-95 or neuroligin 1/3/4. α-Neurexins also induce clustering of the GABA(A) receptor γ2 subunit. This synapse promoting activity of α-neurexins is mediated by the sixth LNS (laminin neurexin sex hormone-binding protein) domain and negatively modulated by upstream sequences. Although inserts at splice site 4 (S4) in β-neurexins promote greater clustering activity for GABA than glutamate proteins in coculture assay, α-neurexin-specific sequences confer complete specificity for GABA proteins. We further report a developmental increase in the ratio of −S4 to +S4 forms of neurexins correlating with an increase in glutamate relative to GABA synaptogenesis and activity regulation of splicing at S4. Thus, +S4 β-neurexins and, even more selectively, α-neurexins may be mediators of GABAergic synaptic protein recruitment and stabilization.